Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the equation [tex]\(2^{7x - 3} = 16\)[/tex], follow these steps:
1. Express 16 as a power of 2:
Notice that 16 can be written as a power of 2: [tex]\(16 = 2^4\)[/tex].
2. Rewrite the equation:
Since [tex]\(2^{7x - 3} = 16\)[/tex] and [tex]\(16 = 2^4\)[/tex], you can equate the exponents of 2. This gives:
[tex]\[ 7x - 3 = 4 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
- Add 3 to both sides of the equation:
[tex]\[ 7x - 3 + 3 = 4 + 3 \][/tex]
Simplifying this, you get:
[tex]\[ 7x = 7 \][/tex]
- Divide both sides by 7:
[tex]\[ x = \frac{7}{7} \][/tex]
Simplifying this, you get:
[tex]\[ x = 1 \][/tex]
So, the solution is [tex]\(x = 1\)[/tex].
Answer:
A. The solution is [tex]\(x = 1\)[/tex]
1. Express 16 as a power of 2:
Notice that 16 can be written as a power of 2: [tex]\(16 = 2^4\)[/tex].
2. Rewrite the equation:
Since [tex]\(2^{7x - 3} = 16\)[/tex] and [tex]\(16 = 2^4\)[/tex], you can equate the exponents of 2. This gives:
[tex]\[ 7x - 3 = 4 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
- Add 3 to both sides of the equation:
[tex]\[ 7x - 3 + 3 = 4 + 3 \][/tex]
Simplifying this, you get:
[tex]\[ 7x = 7 \][/tex]
- Divide both sides by 7:
[tex]\[ x = \frac{7}{7} \][/tex]
Simplifying this, you get:
[tex]\[ x = 1 \][/tex]
So, the solution is [tex]\(x = 1\)[/tex].
Answer:
A. The solution is [tex]\(x = 1\)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.